Rainfall Analysis and Rainfall Recharge of the Papagni River Basin, Andhra Pradesh - Krishnaiah, Y. V. (National Geographical Journal of India, 2022)
The Papagni river basin covering an area of about 8,250 Km’ has been studied using IRS-1B Geo- coded and LISS-III data on scale 1:50,000. The aim of this paper is to analyses the rainfall characteristics that is average rainfall, rainfall intensity, rainfall variability and rainfall ratio of the Papagni river basin. The ground water resources in granitic terrain are restricted to weathered, fissured, jointed, fractured and faulted zones. The water resources and rainfall recharge in the basin are limited due to hard rock nature. The daily rainfall data for a period of 50 years is collected, converted and computed to monthly, seasonal and annual basis for sixteen rain-gauge stations. The average annual precipitation of the basin is 720mm. The average annual recharge of the basin is 89.54mm. The total surface water resources of the basin are 5,940,000,000m. The total ground water resources of the basin have been estimated to be 738,705,000m°>. The present paper attempts to study rainfall analysis of seasonal, annual and rainfall recharge of the Papagni river basin.